2019
DOI: 10.1002/brb3.1192
|View full text |Cite
|
Sign up to set email alerts
|

Neural responses to children’s faces: Test–retest reliability of structural and functional MRI

Abstract: Introduction Functional MRI (fMRI) is commonly used to investigate the neural mechanisms underlying psychological processes and behavioral responses. However, to draw well‐founded conclusions from fMRI studies, more research on the reliability of fMRI is needed. Methods We invited a sample of 41 female students to participate in two identical fMRI sessions, separated by 5 weeks on average. To investigate the potential effect of left‐handedness on the stability of neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 41 publications
4
9
0
Order By: Relevance
“…Using different modelling approaches, we showed fair reliability for simple fMRI measures related to self-blame, but poor reliability for more complex measures. Our findings corroborate previous reports that reliability appears to diminish with increasing model complexity, especially when using contrasts or difference scores ( Hedge et al, 2018 , Gorgolewski et al, 2013 , Fröhner et al, 2019 , Heckendorf et al, 2019 ). Infantolino and colleagues showed that, when two conditions are highly correlated in an individual, subtraction-based difference scores will invariably remove shared variance which is relevant to the internal consistency of the task ( Infantolino et al, 2018 ).…”
Section: Discussionsupporting
confidence: 91%
“…Using different modelling approaches, we showed fair reliability for simple fMRI measures related to self-blame, but poor reliability for more complex measures. Our findings corroborate previous reports that reliability appears to diminish with increasing model complexity, especially when using contrasts or difference scores ( Hedge et al, 2018 , Gorgolewski et al, 2013 , Fröhner et al, 2019 , Heckendorf et al, 2019 ). Infantolino and colleagues showed that, when two conditions are highly correlated in an individual, subtraction-based difference scores will invariably remove shared variance which is relevant to the internal consistency of the task ( Infantolino et al, 2018 ).…”
Section: Discussionsupporting
confidence: 91%
“…For the third participant, fMRI data of the first 156 trials (67% of the task) of Session 2 were available. As we obtained similar reliability of FFA activity in the contrast faces versus scrambled stimuli in previous analyses (see Heckendorf et al, 2018). We included this participant’s FFA activity during the available trials in the analyses.…”
Section: Methodssupporting
confidence: 81%
“…Details concerning MRI image acquisition and fMRI processing and analysis, along with results (observed activation as well as reliability of activity) have been reported elsewhere (Heckendorf et al, 2016; Heckendorf, Bakermans-Kranenburg, Van IJzendoorn, & Huffmeijer, 2018). We analyzed the fMRI data with FSL (FMRIB’s Software Library), FEAT (FMRI Expert Analysis Tool) Version 5.0.4, part of Jenkinson, Beckmann, Behrens, Woolrich, and Smith (2012), and Smith et al (2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been argued that the lack of replicability of empirical results may well be rooted in the fact that experiments tend to focus on a very narrow part of the method space, holding as many factors fixed as possible ( Baribault et al, 2018 ; Elliott et al, 2020 ; Heckendorf et al, 2019 ). To counter this problem, Baribault et al (2018) propose radical randomization , which consists of a combination of many micro-experiments that differ from each other in particular facets—such as the exact stimuli ( t ), or setting ( s )—that could serve as moderators of the treatment effect.…”
Section: Discussionmentioning
confidence: 99%